2016
DOI: 10.1038/srep36581
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of in-situ plasma spray synthesized sub-stoichiometry TiO2−x

Abstract: The thermoelectric properties of sub-stoichiometric TiO2−x deposits produced by cascaded-plasma spray process are investigated from room-temperature to 750 K. Sub-stoichiometric TiO2−x deposits are formed through in-situ reaction of the TiO1.9 within the high temperature plasma flame and manipulated through introduction of varying amounts of hydrogen in the plasma. Although the TiO2−x particles experience reduction within plasma, it can also re-oxidize through interaction with the surrounding ambient atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Conversely, it should be mentioned that another mechanism may account for the significant increase of the conductivity of the material after laser treatment under a nitrogen atmosphere. The partial reduction of TiO 2 into TiO 2− x may also occur in the presence of C. This behavior was described by Lu et al The introduction of oxygen deficiencies with the resultant formation of TiO 2− x is known to increase the electrical conductivity …”
mentioning
confidence: 78%
“…Conversely, it should be mentioned that another mechanism may account for the significant increase of the conductivity of the material after laser treatment under a nitrogen atmosphere. The partial reduction of TiO 2 into TiO 2− x may also occur in the presence of C. This behavior was described by Lu et al The introduction of oxygen deficiencies with the resultant formation of TiO 2− x is known to increase the electrical conductivity …”
mentioning
confidence: 78%
“…The run with relatively high H 2 /Ar ratio produced the lowest porosity was therefore selected for preparation of coatings for final measurements. It has been reported that high H 2 /Ar ratio has an important impact manifesting itself by oxygen depletion and growing electrical conductivity of materials containing Ti‐O bonds . Hence, GSP spraying in the present work can be considered as spraying in reduction conditions.…”
Section: Methodsmentioning
confidence: 96%
“…Harada et al obtained his best zT of 0.12 at 773 K in the hot-pressed specimen of TiO 1.90 . Lee et al demonstrated a high zT value of 0.132 at 750 K for substoichiometric TiO 2– x synthesized by in situ plasma spray . Many other investigations have also been conducted for the thermoelectric performance of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%